PENGARUH KOMBINASI JENIS CENDAWAN ENTOMOPATOGEN DENGAN KERAPATAN KONIDIA TERHADAP INTENSITAS SERANGAN LARVA ULAT GRAYAK - HUMAIROH, DURROH; Prayogo, Yusmani (LenteraBio: Berkala Ilmiah Biologi, 2013)
Armyworm is one of the important pests of soybean. This caterpillar is polifag or can attack different types of crops, vegetables, and fruits. Entomopathogenic fungus is an alternative to control armyworm development. This study aimed to determine the effectiveness of the type and density of entomopathogenic fungi conidia against the intensity of the attacks inflicted armyworm larvae. The research method used was a randomized block design (RBD) two factors. There were 12 treatments with 3 types of fungi include Metarhizium anisopliae, Beauveria bassiana and Lecanicillium lecanii conidia density using 4 types namely 106, 107, 108 and 109 conidia/ml. Each treatment was repeated 3 times. Data such as the percentage of the intensity of the attacks by the larvae at 7 days after application were analyzed using two-way analysis of variance. The results showed that the combination of the fungus Metarhizium anisopliae conidia density 108 is effective in controlling the intensity of the attacks to 34.74%